(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Organobismuth chemistry offers unique opportunities for developing selective reagents and catalysts due to the element’s accessible Bi(III)/Bi(V) redox states, pronounced Lewis acidity, and comparatively low toxicity among heavy elements. In this study, more than 150 previously unreported bismuth derivatives were synthesized, with 74 structures determined by single-crystal X-ray diffraction. Particular attention was given to tetraphenylbismuth aryloxides, which are obtained in high yields under mild conditions through the phenyl–proton exchange reaction between pentaphenylbismuth and phenols. to seven, producing systematic perturbations in equatorial bond angles.